Implementation of The Obligation To Provide Free Notarial Services For Underprivate People In Malang - Arsy Azuhra; Istislam; R. Imam Rahmat Sjafi'i (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
The implementation of the obligation to provide free notarial services in Malang City has not been effective as mandated in Article 37 paragraph (1) of Law Number 2 of 2014 concerning the Notary Position (UUJN). The provisions that emphasize the obligation of notaries to provide free legal services to the underprivileged have not been fully implemented due to the absence of implementing regulations governing the mechanism, recipient criteria, and supervision procedures. The results of the study indicate that most notaries only provide pro bono services to clients whose economic conditions are known, so that implementation is subjective, sporadic, and non-standardized. The main obstacles in its implementation are divided into three aspects, namely structural, normative, and sociological. From the structural side, the lack of public knowledge and the absence of technical guidelines are the main obstacles. From the normative aspect, there is no clear definition regarding the criteria for